August Wilson and Black Aesthetics - Shannon, S. author. aut Link
VI, 225 p.
Keywords: This book offers new essays and interviews addressing Wilson's work, ranging from examinations of the presence of Wilson's politics in his plays to the limitations of these politics on contemporary interpretations of Black aesthetics. Also includes an updated introduction assessing Wilson's legacy since his death in 2005.